Flow of thin films on patterned surfaces - Kondic, L. (2003)
We present fully nonlinear time-dependent simulations of the gravity driven flow of thin wetting liquid films. Thecomputations of the flow down a homogeneous substrate show that the contact line where liquid, solid, and gas phasemeet becomes unstable and develops patterns. These computations are extended to inhomogeneous surfaces, and showthat inhomogeneity can induce instability of the fluid front. In particular, we analyze flow on patterned surfaces, wheresurface inhomogeneity is introduced in a controllable manner. We discuss the conditions that need to be satisfied sothat surface patterns, lead to predictable selective wetting of the substrate. Applications of these results totechnologically relevant flows are discussed.